Sexual health preparedness among medical students - Merhavy, Z.I.; Varkey , T.C.; Kotyk , T.; Zeitler , C. (Medicni Perspektivi, 2023)
It has been found that many medical students and early career physicians express feelings of being unprepared and undereducated on topics relating to patient sexual health. Based on previous reports on the topic, the quality and quantity of sexual health education in medical school has been minimally improved over the last several years. Aim of the work is to identify possible deficiencies in sexual health preparation within current medical education curriculum among United States allopathic, osteopathic, and Caribbean medical programs. Medical students (n=100) from three different medical program types, including United States allopathic (n=31), United States osteopathic (n=23), and Caribbean allopathic program (n=46), and years of study (1-4), were recruited informally and participated in a 15-question survey regarding their perceptions and experience of sexual health education, training, and preparation at their respective medical school. After obtaining informed consent, students completed this survey through a private form and the data was compared to students of different years, different programs, and different intended specialties. With a sample size of 100 students from three different medical school programs, it was clear that most schools provide some level of sexual health education to students, however, in most cases, the education received was overall perceived as less than adequate by the students. Additionally, it was seen that almost every student indicated a need for their respective institution to provide additional training in both basic sciences as well as in their clinical education to feel more confident in their ability to discuss sexual health priorities with their patients. Current practices in medical education continue to fail to meet student expectations. To create more competent and confident physicians to adequately assist patients in their sexual health needs, more positive curriculum changes need to be made in order to establish a new, higher standard for quality of sexual health care. Small changes at the pre-clinical and clinical level can improve overall student preparedness and confidence when discussing sexual health with patients.